تأثير طريقة الصورة والصورة على ذكر المفردات العربية لطالبات الفصل السابع بالمدرسة الثانوية السلفيّة الشّافعيّة سبلاك جومبانج - Siti Sofiyati Zein; Abdul Qodir (Program Studi Pendidikan Bahasa Arab, 2023)
This study examines how the use of Picture and Picture Method to seventh grade students at MTs. Salafiyah Syafi'iyah Seblak Jombang? How is the memory of Arabic vocabulary for seventh grade students at MTs. Salafiyah Syafi'iyah Seblak Jombang? How is the effect of Picture and Picture method on the memory of Arabic vocabulary to seventh grade students at MTs. Salafiyah Syafi'iyah Seblak Jombang? This research method involves quantitative research data collection, tests, and documentation. Then analyzed with one group pretest-posttest sample. The results of the study: 1) The use of picture and picture method affects students' memory in remembering Arabic vocabulary in class VII-D MTs. Salafiyah Syafi'iyah Seblak Jombang. Judging from the results of the posttest test, the minimum value is 70, the maximum value is 95, and the average value is 78.33. 2) Students' memory in using the picture and picture method is influential in class VII-D MTs. Salafiyh Syafi'iyah Seblak Jombang. Judging from the results, the average value of the pretest test is 62.14, and the posttest test is 78.33. 3) From data collection, using Picture and picture method on Arabic vocabulary memory has a significant effect. This can be seen from the average value of class VII-D which uses the Picture and picture method, with an average value of 78.33. After being tested for normality, the data is normally distributed with a value of 00.91. If the hypothesis value is 00.000, then Ha is accepted and Ho is rejected.